2022
DOI: 10.3389/fsurg.2022.1012160
|View full text |Cite
|
Sign up to set email alerts
|

A modified trajectory of kyphoplasty via superior pedicle notch for osteoporotic vertebral compression fractures: Technique note and clinical result

Abstract: BackgroundPercutaneous extra-pedicular kyphoplasty can achieve better clinical results than transpedicular kyphoplasty. However, lumbar segment artery injury as a disaster complication limits its clinical application.ObjectiveTo describe and evaluate a modified trajectory of kyphoplasty for the treatment of osteoporotic vertebral compression fractures (OVCF).MethodsEighty-one patients who underwent percutaneous kyphoplasty (PKP) for lumbar OVCF at our hospital between May 2017 and May 2021 were enrolled. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…At present, grafting of the injured vertebral bone primarily involves intravertebral bone grafting via the narrow vertebral pedicle channels, increasing treatment difficulty and possibly leading to complications such as vertebral pedicle fracture and nerve root injury [8]. In contrast, bone grafting via superior pedicle notch approach is a relatively safer approach [9,10]. The superior pedicle notch is located below the intervertebral foramen and is a "safe zone" with no vascular nerves in the surroundings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, grafting of the injured vertebral bone primarily involves intravertebral bone grafting via the narrow vertebral pedicle channels, increasing treatment difficulty and possibly leading to complications such as vertebral pedicle fracture and nerve root injury [8]. In contrast, bone grafting via superior pedicle notch approach is a relatively safer approach [9,10]. The superior pedicle notch is located below the intervertebral foramen and is a "safe zone" with no vascular nerves in the surroundings.…”
Section: Discussionmentioning
confidence: 99%
“…The superior pedicle notch is located below the intervertebral foramen and is a "safe zone" with no vascular nerves in the surroundings. Jiang et al [10] have reported that the superior pedicle notch approach to PVP has a higher angle of abduction and sagittal view, therefore preventing neurovascular injury and decreasing radiation exposure and operation time. The superior pedicle notch is located in the upper one-third of the vertebral body and is adjacent to the "shell", providing an anatomical basis for the reconstruction of the injured spine.…”
Section: Discussionmentioning
confidence: 99%